Instrument Readiness Sebagai Faktor Yang Berpengaruh Terhadap Intensi Berwirausaha Mahasiswa - Herwiek Diyah Lestari; Ady Achadi (FEB UNWIKU PURWOKERTO, 2022)
This study aims to analyze the effect of instrument readiness on the intensity of student entrepreneurship. This research was conducted on students of the Management Study Program, Faculty of Economics and Business, Wijayakusuma University, Purwokerto. The number of samples used were 65 respondents, and the sampling technique used was simple random sampling method. To determine the sample size using the method developed by Isaac and Michael. The analytical tool used is Multiple Linear Regression (Multiple Regression). The results of the analysis using multiple linear regression obtained coefficient values ​​from Capital Through (b1 = 0.284), Information Availability (b2 = 0.642), and Networking (b3 = 0.371) and by using a 95% Confidence level (α = 0.05) and degrees of freedom (df)= (nk) = (65-4)= 61 then the t table is 1.999. While the t-count for each independent variable is Capital Through (th1=3.251), Information Availability (th2=7.672), and Networking (th3=6.715). Because th1, th2, th3 > ttable, then Ho is rejected. This can be interpreted that Capital Through, Availability of Information, and Networks have a positive and significant effect on Entrepreneurial Intentions of Students of the Faculty of Economics and Business Unwiku. This shows that the better the Instrument Readiness Dimensions which consist of Capital Through, Available Information, and Networking are owned, the more the intensity of the students of the Faculty of Economics and Business for entrepreneurship is increased. Keywords: Capital Through, Information , Networking, and Entrepreneurship Intentions